Inventariando o Cemitério Nossa Senhora da Piedade : patrimônio cultural e ensino de História no espaço dos mortos e de sociabilidade dos vivos - Araujo, Francisca Nailê Bernardo de (2020)
In order to boost History classes beyond the school walls, this research and production of knowledge about history teaching was carried out at the Nossa Senhora da Piedade Cemetery in the city of Cuiabá, built in the late 19th century, presenting possibilities of study and historical reflection in the field of Heritage Education, in the space of the dead and sociability of the living, in the capital of the state of Mato Grosso. Thus, this proposal opens a perspective of teaching and research, based on the study of the territoriality of the city cemetery, with high school students, providing the opportunity to learn about Local History, and, at the same time, the development of Heritage Education aimed at the awareness of preservation of the historical spaces of the city of Cuiabá. Thus, with the study of Local History, strategies and methodologies are constituted in this work in order to approximate the teaching of History and the reality experienced by students, in the sense of thinking about meaningful learning and also active methodologies, according current curriculum guidelines. For the development of this research, the urban territory of the Nossa Senhora da Piedade cemetery was chosen, one of the oldest in the city of Cuiabá, which, in addition to its usual function, is here conceived as a cultural heritage and, therefore, as a place of teaching. and history learning that provides a reading of the history, culture and memory of a city. Through the Heritage Education methodology, with the departure of the classroom to the cemetery, we sought to provide the construction of historical knowledge, evidenced from the narratives elaborated by the students during the application of the elective discipline project and at its closure. This dissertation presents the results of a work carried out in practice, having in the production of the students of the book Memórias de Minha Cidade, one of its main results, constituting the object of analysis of this research. Thus, interving in the daily life of a basic education school in the state education network in Cuiabá, capital of Mato Grosso, the experiences experienced are presented as didactic possibilities for teaching and learning historical knowledge in this urban territory, considered a space for the dead and sociability of the living.